Punt Politics as Failure of Health System Stewardship: Evidence from the COVID-19 Pandemic Response in Brazil and Mexico - Felicia Marie Knaul; Michael Touchton; Héctor Arreola-Ornelas; Rifat Atun; Renzo JC Calderon Anyosa; Julio Frenk; Adolfo Martínez-Valle; Tim McDonald; Thalia Porteny; Mariano Sánchez-Talanquer; Cesar Victora (Elsevier, 2021)
We present a new concept, Punt Politics, and apply it to the COVID-19 non-pharmaceutical interventions (NPI) in two epicenters of the pandemic: Mexico and Brazil. Punt Politics refers to national leaders in federal systems deferring or deflecting responsibility for health systems decision-making to sub-national entities without evidence or coordination. The fragmentation of authority and overlapping functions in federal, decentralized political systems make them more susceptible to coordination problems than centralized, unitary systems. We apply the concept to pandemics, which require national health system stewardship, using sub-national NPI data that we developed and curated through the Observatory for the Containment of COVID-19 in the Americas to illustrate Punt Politics in Mexico and Brazil. Both countries suffer from protracted, high levels of COVID-19 mortality and inadequate pandemic responses, including little testing and disregard for scientific evidence. We illustrate how populist leadership drove Punt Politics and how partisan politics contributed to disabling an evidence-based response in Mexico and Brazil. These cases illustrate the combination of decentralization and populist leadership that is most conducive to punting responsibility. We discuss how Punt Politics reduces health system functionality, providing lessons for other countries and future pandemic responses, including vaccine rollout.